A Novel Treatment of Acne Fulminans with Adalimumab: A Case Report - Rajaii, Roxanne (Spartan Med Res J, 2018)
Acne fulminans (AF) is a rare and highly inflammatory severe form of acne most commonly seen in adolescent males. Unlike acne vulgaris, AF presents with associated systemic manifestations including, but not limited to, malaise, myalgia, arthralgia, fever, anorexia, and weight loss. It is often an extremely painful condition of sudden onset and can occur years after mild or moderate acne vulgaris. While the inciting agent for this condition has been postulated to be an explosive hypersensitivity reaction to the bacterium Propionobacterium acnes, increased androgens, namely testosterone, have also been reported to play a role in the pathogenesis of this disease process. Additionally, environmental triggers such as air pollution and exposure to halogenated hydrocarbons during occupational activities in enclosed, high temperature settings have been identified as possible etiologies or exacerbating factors. AF is primarily a clinical diagnosis. Isotretinoin, in combination with systemic steroids, are generally the treatments of choice for this disease entity. A Caucasian male in his early 40’s presented to the authors’ clinic with a chief complaint of painful acneiform nodules, cysts, papules, pustules, and abscesses on his back, chest, neck, shoulders, upper arms, and thighs for several months. This case report demonstrates a refractory case of AF with significant clinical improvement after six weeks of topical treatment with subcutaneous adalimumab in combination with oral doxycycline. This case provides evidence supporting the role of Adalimumab in the treatment of AF in addition to the other inflammatory conditions currently FDA approved for treatment with this tumor-necrosis factor (TNF) alpha inhibitor. These conditions include plaque psoriasis, Crohn’s disease, hidradenitis suppurativa, psoriatic arthritis, and rheumatoid arthritis.